Pilea microphylla Artillery Plant: FPS479/FP479, 6/2007 - Gilman, Edward (EDIS, 2007)
This document provides an overview of the artillery plant (Pilea microphylla), detailing its characteristics, growth habits, and uses. The plant is described as a fine-textured, fern-like ground cover that grows 8 to 12 inches tall and spreads up to two feet wide. It thrives in USDA hardiness zones 10B through 11 and prefers well-drained, moist soils. The artillery plant is suitable for mass planting, container gardening, and indoor growth. It is noted for its moderate drought tolerance, potential invasiveness, and occasional pest issues. Propagation is typically done through cuttings, and the plant requires minimal maintenance, with occasional pinching to encourage bushiness. Original publication date October 1999.